Debt maturity structure of low and high Tobin's Q firms - Benjie, Lee Chien Jiang (2014)
This study examines the effects of growth in influencing debt maturity structure of Malaysian companies. The result shows that growth firms with high Tobin’s Q are indifferent between short-term and long-term debt financing. However, the relationship between growth and debt maturity is negatively related for firms with low Tobin’s Q. Therefore, this implies that growth firms with high Tobin’s Q do not make use of debt maturity structure to mitigate the agency cost of debt caused by underinvestment problem, while growth firms with low Tobin’s Q maintain higher levels of short-term debt, but lower levels of long-term debt to mitigate agency cost of equity caused by overinvestment problem